Manipulation of Group-Velocity-Locked Vector Solitons From Fiber Lasers - X. X. Jin; Z. C. Wu; L. Li; Q. Zhang; D. Y. Tang; D. Y. Shen; S. N. Fu; D. M. Liu; L. M. Zhao (IEEE Photonics Journal, 2016)
Manipulation of group-velocity-locked vector solitons (GVLVSs) is numerically proposed and experimentally demonstrated. A pseudo-high-order GVLVS could be generated from a fundamental GVLVS with the help of a polarization-resolved system. Specifically, a pseudo-high-order GVLVS with a two-humped pulse along one polarization and a single-humped pulse along the orthogonal polarization could be obtained. The phase difference between the two humps could be 180°.